Inhibition of SALL4 reduces tumorigenicity involving epithelial-mesenchymal transition via Wnt/β-catenin pathway in esophageal squamous cell carcinoma. Issue 1 (December 2016) - He, Jing; Zhou, Mingxia; Chen, Xinfeng; Yue, Dongli; Yang, Li; Qin, Guohui; Zhang, Zhen; Gao, Qun; Wang, Dan; Zhang, Chaoqi; Huang, Lan; Wang, Liping; et al.
Abstract Background Growing evidence suggests that SALL4 plays a vital role in tumor progression and metastasis. However, the molecular mechanism of SALL4 promoting esophageal squamous cell carcinoma (ESCC) remains to be elucidated. Methods The gene and protein expression profiles- were examined by using quantitative real-time PCR, immunohistochemistry and western blotting. Small hairpin RNA was used to evaluate the role of SALL4 both in cell lines and in animal models. Cell proliferation, apoptosis and invasion were assessed by CCK8, flow cytometry and transwell-matrigel assays. Sphere formation assay was used for cancer stem cell derivation and characterization. Results Our study showed that the transcription factor SALL4 was overexpressed in a majority of human ESCC tissues and closely correlated with a poor outcome. We established the lentiviral system using short hairpin RNA to knockdown SALL4 in TE7 and EC109 cells. Silencing of SALL4 inhibited the cell proliferation, induced apoptosis and the G1 phase arrest in cell cycle, decreased the ability of migration/invasion, clonogenicity and stemness in vitro. Besides, down-regulation of SALL4 enhanced the ESCC cells' sensitivity to cisplatin. Xenograft tumor models showed that silencing of SALL4 decreased the ability to form tumors in vivo. Furthermore, our study demonstrated that SALL4 played a vital role in modulating the stemness of ESCC cells via Wnt/β-catenin signaling pathway and in epithelial-mesenchymal transition. Conclusions Our results revealed that SALL4 might serve as a functional marker for ESCC cancer stem cell, a crucial marker for prognosis and an attractive candidate for target therapy of ESCC.